PEMBERIAN LAYANAN KESEHATAN DAN GIZI PADA ANAK USIA DINI MELALUI KEGIATAN POSYANDU DI DESA PURNAJAYA SEBAGAI KESIAPAN IMPLEMENTASI PAUD HI - Ananda Paramita (JURNAL ILMIAH PENELITIAN MAHASISWA, 2024)
Thisactivitywas carried out tointroducePAUD HI tothePurnajaya villagecommunity, as well as to find out the level of health and nutrition service delivery for early childhood through Posyandu activities.Thepurposeofthisserviceistodeterminethelevelofhealthandnutritionservicedelivery forearlychildhoodinPurnajayaVillageasoneoftherequirementsfortheimplementationofPAUD HI.IndrodectiontoPAUDHIiscarriedoutthroughoutreachactivities,whichwasattendedbythree villages in the Indralaya utara sub-district.Thisresearch data collection technique isdivided into 3 types, namely observation, interviews, and documentation. The results obtained indicate that Kota Raya Village has been able to meet the needs of early childhood health and nutrition services to implement PAUD HI, in the form of recording health, height, weight, administration of vitamins, and immunizations for children.